(untitled) (Biodiversitas Journal of Biological Diversity, 2008)
The impact of CPO (Crude Palm Oil) dock activity in Mentaya River of Central Borneo caused degradation of ecosystem, particularly on both mangrove and macrozoobenthos community. One of methods used for monitoring of ecosystem degradation was to determine species that were still survive under the polluted conditions. These survival species were assumed to synthesize alloenzyme that can be used as indicator. Alloenzyme was synthesized as an effort of adaptation processes toward environmental pressures caused by CPO spill on Mentaya River. Alloenzyme would be expressed as phenotypic and genotypic adaptation processes or phenotypic plasticity. Research was carried out, consisted of field research included collecting sample and environmental data (oil content, temperature, pH, electric conductivity and redox potential), and laboratory research included series analysis of water quality (DO, BOD, COD, pH, TSS, TDS) and also alloenzyme content of Soneratia caseolaris L. and Macrobrachium rosenbergii de Man. The alloenzyme of root and leaves mangrove and prawnâ€™s hepatopancreas was analyzed using Spencer starch gel electrophoresis modified method of exposed on sucrose solution. Separated components of alloenzyme were detected by special staining for Esterase isozyme. The results revealed that Soneratia caseolaris L. and Macrobrachium rosenbergii de Man were bioindicator organisms for the polluted site by oil spills from CPO loading activities. The polluted river water by oil spill from CPO activities decreased redox potential, DO, increased oil content, DHL, water temperature, pH sediment, pH water, TDS, BOD, COD, TSS. Gel electrophoretical analysis demonstrated that Mangrove Soneratia caseolaris synthesized alloenzyme consisted of complex enzymes such as EST in its root and leave cells. Those enzymes were nearly similar to those of Macrobrachium rosenbergii. The oil spill from CPO have ester bonding so its adaptation mechanism with release Esterase isozyme to hodrolysis process. The similar component of the isozyme are promising enzyme used as a tool for biomonitoring and an effective methods for detection of early river ecosystem degradation. Â© 2008 Jurusan Biologi FMIPA UNS Surakarta Key words: CPO, Isozym